The stage-specific impairment of granulopoiesis in people living with HIV/AIDS (PLWHA) with neutropenia. Issue 4 (14th February 2020) - Fan, Lina; Han, Junyan; Xiao, Jiang; Dai, Guorui; Hao, Yu; Yang, Di; Liang, Hongyuan; Wu, Liang; Song, Chuan; Li, Guoli; Li, Bei; Wang, Di; et al.
Abstract: Neutropenia and impaired functions were common manifestation in antiretroviral therapy (ART) in both naïve and experienced PLWHA. Granulopoiesis can be divided into two phases: lineage determination and committed granulopoiesis. However, stage-specific impairment of granulopoiesis in PLWHA with neutropenia remains unclear. A total of 48 ART-naïve and 49 ART-experienced PLWHA from 2016 to 2018 were recruited and divided into non-, mild-, and moderate-to-severe-neutropenia groups according to their neutrophil counts. The bone marrow aspirates and peripheral blood were collected and analyzed by multicolor flow cytometry for granulocyte subsets, hematopoietic stem/progenitor cells (HSPC), apoptosis, and emigration and retention of different subsets. Compared with healthy donors, the percentages of circulating segmented neutrophils were significantly decreased along with an increase of immature neutrophils in both groups. ART-naïve patients with moderate to severe neutropenia exhibited decreased proportion and accelerated apoptosis of relative mature segmented neutrophils. In contrast, ART-experienced patients with neutropenia displayed decreased proportion of granulocyte macrophage progenitors, indicating a defect at a stage of lineage determination. Meanwhile, ART-experienced patients with neutropenia also the expression of CXCR4 segmented neutrophils, suggesting an increased retention of segmented neutrophils inn the bone marrow. ART-naïve patients with neutropenia is caused by increased apoptosis of relatively differentiated neutrophils at committed granulopoiesis, whereas impaired lineage determination and enhanced retention of segmented neutrophils contribute to in ART-experienced patients.